2011
DOI: 10.1523/jneurosci.1745-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Evidence for the Involvement of the Macaque Ventrolateral Prefrontal Area 12r in Controlling Goal-Directed Actions

Abstract: The macaque ventrolateral prefrontal (VLPF) area 12r is thought to be involved in higher-order nonspatial information processing. We found that this area is connectionally heterogeneous, and the intermediate part is fully integrated in a cortical network involved in selecting and controlling object-oriented hand and mouth actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 62 publications
7
90
0
Order By: Relevance
“…Indeed, both sensory-driven (forward model) and internally generated (generative model) representations of the same observed action seem to be recruited in a predictable context: the former are mainly based on Action MN activity, the latter mostly rely on the predictive activation of Inaction MNs. This proposal fits with the available anatomical data showing that, in area F5, there is a convergence of information from the superior temporal sulcus, through the inferior parietal cortex, concerning others' observed actions, and from the higher order prefronto-dependent motor (Luppino et al, 1993;Gerbella et al, 2011) and prefrontal (Borra et al, 2011;Gerbella et al, 2013) areas. Thus, the MN system can play a role both in sensory-driven action representation, through the parietofrontal sensorimotor pathway, and context-based action prediction, through the prefronto-premotor routes, although these processes appear to rely on partially distinct neuronal populations.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, both sensory-driven (forward model) and internally generated (generative model) representations of the same observed action seem to be recruited in a predictable context: the former are mainly based on Action MN activity, the latter mostly rely on the predictive activation of Inaction MNs. This proposal fits with the available anatomical data showing that, in area F5, there is a convergence of information from the superior temporal sulcus, through the inferior parietal cortex, concerning others' observed actions, and from the higher order prefronto-dependent motor (Luppino et al, 1993;Gerbella et al, 2011) and prefrontal (Borra et al, 2011;Gerbella et al, 2013) areas. Thus, the MN system can play a role both in sensory-driven action representation, through the parietofrontal sensorimotor pathway, and context-based action prediction, through the prefronto-premotor routes, although these processes appear to rely on partially distinct neuronal populations.…”
Section: Discussionsupporting
confidence: 82%
“…This view has received convergent support from several neurophysiological studies, indicating that some sensory description of the ongoing movement is always necessary to trigger MN response (Umiltà et al, 2001;Kohler et al, 2002;Fogassi et al, 2005;Maranesi et al, 2013). Maranesi et al (2013) demonstrated that, at the population level, MN response to an observed agent's reaching-grasping action starts ϳ60 ms after movement onset, supporting the idea that MNs generate a reactive, sensory-driven representation of observed actions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We put the border between dlPFC and vlPFC at 3 mm ventral to the principal sulcus. Thus, the dlPFC and vlPFC largely corresponded to area 46d/46v/9 and area 45/12, respectively (Petrides andPandya, 1999, 2002;Borra et al, 2011;Gerbella et al, 2012). In total, we found 1149 taskrelated lPFC neurons: 358 in the vlPFC (255 in monkey 1 and 103 in monkey 3) and 791 in the dlPFC (397 in monkey 1 and 394 in monkey 3).…”
Section: Resultsmentioning
confidence: 72%
“…Is there an insulocortical circuit that may transmit vitality form information to the cortex? Anatomical data in the monkey support this possibility by showing that the dorsocentral sector of the insula has rich connections with areas AIP (9), F5 (10), and 12r (11) [that is, with the parietal and frontal areas that form the circuit involved in the organization of arm movements in the monkey (18,19) as well as humans (20)(21)(22)] (Fig. 3A).…”
Section: Discussionmentioning
confidence: 95%